Implementasi Kebijakan Program Monitoring Dan Aspirasi Publik Melalui Media Massa Di Lingkungan Pemerintah Provinsi DKI Jakarta (Studi Kasus Dinas Komunikasi, Informatika dan Statistik DKI Periode Januari-Desember 2019) - Angga Noviar; Achmad Lutfi (Jurnal Reformasi Administrasi : Jurnal Ilmiah untuk Mewujudkan Masyarakat Madani, 2020)
The purpose of this paper is to find out the implementation of monitoring program and media news analysis within the Jakarta Capital City Government managed by Department of Communication, Information and Statistics for Jakarta through the Public Opinion and Aspirations Management Unit. Every aspiration conveyed by the public through the reader letter in the mass media will be analyzed, managed and followed up by the relevant instruments. Furthermore, these public aspirations will be utilized by local governments to determine the direction of development policies. In its implementation, 85% of public aspirations were not responded by related instruments. To find solutions to existing problems the author uses theories from Replay and Franklyn. Data collection from the management unit of public opinion and aspirations in the form of activity documents, reference books and journals on public policy implementation and mass media communication, as well as interviews with stakeholders. In this study, the data obtained were analyzed qualitatively. In the research process found several obstacles in the internal unit so that the targets and objectives have not been achieved, including: there are still implementers who do not carry out standard operational procedures and officers that un-routinely forward and reply emails of analyzed aspirations to the relevant regional. This paper concludes that the implementation of the media news monitoring and analysis program in the Jakarta Capital City Government is not yet on target because of the low level of compliance and smooth implementation.